The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1748-7161-4-s1-o3
|View full text |Cite
|
Sign up to set email alerts
|

Changing a "progressive" factor into a "corrective" factor: the effect of intervertebral disc modulation in treatment of idiopathic scoliosis

Abstract: BMI is a surrogate measure for body fat and circulating leptin levels. The finding that girls with relatively lower BMI have significantly later menarche, and a significant excess of TAs, suggests a relation to energy homeostasis through the hypothalamus. The hypothesis we suggest for the pathogenesis of severe TA in girls and boys has the same mechanism as that proposed recently for AIS girls, namely: severe TAs are initiated by a genetically-determined selectively increased hypothalamic sensitivity (up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The study of the radiographical assessment of our referred school scoliosis screening children suffering mild IS showed that the deformity starts at the level of the intervertebral disc, then the vertebra body, as a result of the plasticity of the intervertebral disc [8,9]. Three years later, this finding was confirmed in another report [15].…”
Section: Intervertebral Disc and Adolescent Idiopathic Scoliosismentioning
confidence: 78%
See 2 more Smart Citations
“…The study of the radiographical assessment of our referred school scoliosis screening children suffering mild IS showed that the deformity starts at the level of the intervertebral disc, then the vertebra body, as a result of the plasticity of the intervertebral disc [8,9]. Three years later, this finding was confirmed in another report [15].…”
Section: Intervertebral Disc and Adolescent Idiopathic Scoliosismentioning
confidence: 78%
“…It was discovered that the younger children with truncal asymmetry who were referred to the scoliosis clinic often times had a perfectly straight spine with no vertebral rotation, despite the presence of a thoracic hump [7]. The scoliotic spine first deforms at the level of the intervertebral disc, not the vertebrae [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hueter–Volkman law, which is the rationale for the management of scoliosis during skeletal growth, explains this “vicious cycle” of asymmetrical growth. The law assumes that growth follows a biomechanical mode of deformity progression in which increased axial compression decelerates growth and reduced axial compression accelerates growth in the skeletally immature (Grivas, Vasiliadis, Rodopoulos, Bardakos, & Gatos, 2009). The Hueter–Volkmann theory is the basis for explaining the relationship in which wedging of the IVD contributes to the progression of IS.…”
Section: Pathophysiologymentioning
confidence: 99%
“…For growth to proceed harmoniously, the developing mechanical properties of the disc must remain in synchronicity with these rapidly increasing loads [3]. In case of a mismatch between increasing asymmetrical spinal loading, and mechanical maturation of the IVD, spinal deformity may develop [3,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%